Quantitative methods to study the effectiveness of public administration to ensure energy security - Arginbayeva, G.M.; Amirbekuly, Е.; Sailaubekov, N.T. (BUKETOV BUSINESS REVIEW, 2018)
The main purpose of this article is to form an aggregated indicator of energy security (IEE) based on individual indicators. These indicators reflect the energy, economic, social and environmental aspects of energy security that were developed in 1995 by the World Economic Council. This article describes the principles and methodology used to develop the energy security indicator, and authors also uses modern methods of econometric analysis and data processing methods, such as the main component method. This method allows determining the group of indicators that have the biggest impact on energy security, and using different scenarios of energy policy to assess their effectiveness. Since the indicator of energy security reflects the state of the country's energy sector, its assessments will help in improving energy policy and public administration. This is due to the fact that the calculation of this index includes indicators that reflect the main factors of state policy in the energy sector. Thus, the indicator of energy security can help in identifying problems in the energy sector of the country and develop ways to eliminate them. It can also be used for comparative analysis with various countries in order to use their best practices.